Morphological differences in populations of Jacobaea erucifolia: Genetic differentiation, phenotypic plasticity or ecotypes? - Barbara Gawrońska; Małgorzata Marszałek; Piotr Kosiński; Joanna Zeyland; Leszek Bednorz (PLoS ONE, 2025)
Accurate taxonomic classification is essential for effective conservation strategies, especially for rare and endangered species. Traditionally based on morphology, such classifications may be challenged by recent advances in molecular tools that reveal hidden genetic structure or lack thereof. Jacobaea erucifolia is a declining species in Poland, primarily threatened by habitat loss, fragmentation, and competition with invasive species. Although two subspecies—erucifolia and tenuifolia—have been identified in Poland based on leaf morphology and ecological preferences, the taxonomic status of these forms remains unclear. This study aimed to evaluate the genetic variation within ten Polish populations of J. erucifolia and assess whether the observed morphological differences correspond to genetic divergence. Based on morphology, four populations were classified as subsp. erucifolia and six as subsp. tenuifolia. Reference populations of confirmed subspecies tenuifolia were included from Slovakia, Hungary, and the Netherlands. Genetic analyses were conducted using amplified fragment length polymorphisms (AFLPs), chloroplast DNA restriction fragments (RFLP), cpDNA, and nuclear internal transcribed spacer (ITS) ribosomal DNA sequences. The results revealed a high level of admixture and no significant genetic differentiation among Polish populations, regardless of their initial morphological classification. All Polish populations formed a single genetic group, distinct from foreign tenuifolia samples, although no diagnostic genetic markers were identified to separate these two groups (subspecies) of J. erucifolia definitively. Moreover, sequence data showed no differences among all analyzed individuals, further challenging the validity of subspecies differentiation. These findings suggest that the morphological variation observed within Polish populations likely reflects phenotypic plasticity rather than subspecies-level divergence. Consequently, subspecies tenuifolia does not appear to occur in Poland, and observed differences between Polish populations and those from neighboring countries may represent ecotypic variation. Our study underscores the necessity of integrating genetic and morphological data when resolving taxonomic ambiguities, especially in the context of conservation planning. Future research involving broader geographic sampling and deeper analysis of hybridization patterns will help clarify the evolutionary history and and population dynamics of J. erucifolia.